Online travel agencies (OTAs) e-service quality, brand image, customer satisfaction and loyalty / Wan Nur Fasihah Wan Jasni ...[et al.] - Wan Jasni, Wan Nur Fasihah; Jamaluddin, Mohd Raziff; Hanafiah, Mohd Hafiz (Faculty of Hotel and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2020)
This research aims to analyse the influence of e -service quality and brand image on customer satisfaction and customer loyalty of using online travel agencies (OTAs) in Malaysia. This is a cross-sectional study, and the target population for this research includes all Malaysian customers that use OTA for travel bookings. Structural equation modelling (SEM) procedures were conducted to confirm the research framework and test the research hypotheses. This study confirms that e-service quality positively enhances customer satisfaction and loyalty. However, this study found that brand image would no influence loyalty even though brand image significantly influences customer satisfaction. The results of the study provide an explanation in regards to OTA’s customer satisfaction and loyalty in Malaysia. The findings of this present would significantly contribute to both theoretical and academic aspect that is relevant to tourism and the online travel agency in general.